Cross cultural adaptation of the Repeatable Battery for the Assessment of Neuropsychological Status to a Sinhala speaking clinical population in Sri Lanka - Paranawithana, Chrishara; De Zoysa, Piyanjali (My University, 2012)
Sri Lanka has a dearth of culturally validated neuropsychological tests. Hence, the purpose of this study was to validate the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) in a clinical sample (patients diagnosed with schizophrenia) of 20 to 50year-old Sinhala speaking persons in Sri Lanka. RBANS seemingly possessed good psychometric properties, suitable for adaptation in the Sri Lankan setting, where the uses of locally developed psychometric tests, or globally validated international tests, are scarce. It is also apparent that cognitive assessment of individuals affected by psychiatric conditions (such as schizophrenia) has not become central to everyday clinical practice in Sri Lanka (De Silva and Gunatilake, 2002).